The Influence Of The Work Environment, Emotional Intelligence, And Job Characteristics On Employee Performancesimpang Empat District Office, Asahan District - Eliyana, Eliyana; Susanty Hasibuan, Desi; Yulistiwati Sembiring, Irma; Tua Sidabalok, Salamat Parulian; Gustina Pane, Sri; Rahayu, Sri (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2024)
This research aims to analyze the influence of the work environment, emotional intelligence, and job characteristics on employee performance at the Simpang Empat District Head Office, Asahan Regency. This research uses a survey method with a questionnaire as a data collection instrument. Respondents consisted of employees at the Simpang Empat Subdistrict Office who were chosen randomly. The sample in this study amounted to 33 people. The research results show that the work environment partially has a positive effect on employee performance; emotional intelligence partially has a positive effect on employee performance; job characteristics partially have a positive effect on employee performance; and the work environment, emotional intelligence and job characteristics simultaneously have a positive effect on employee performance. Job characteristics have also been proven to have a significant effect on employee performance. Aspects such as job variety, responsibility, and autonomy at work have a positive correlation with employee performance. With variety and appropriate responsibilities, employees tend to be more motivated and high-performing